Crystallization Behavior of Thermotropic Liquid Crystalline Polymer Reinforced Polyamide 66 in Situ Composites. Issue 3 (March 2014) - Yue, Qunfeng; Zhu, Chuncheng; Yang, Shengrong
This paper studies the non-isothermal crystallization kinetics of polyamide 66 (PA66) and thermal liquid crystal polymer (TLCP) in situ composites with contents of TLCP is 1 wt.% by differential scanning calorimetry (DSC) at various cooling rates. The results show that TLCP acts as nucleator for PA66 matrix accelerating the crystallization. It is speculated, from Avrami exponent and Liu method, that there is a strong hydrogen bonds between –NH-, -CO- groups of PA66 and -COOH and/or -OH groups of TLCP. Kissinger method is employed to obtain the activation energy of the crystallization process and the results indicated that the addition of TLCP may entice the crystallization of PA66 matrix.